The Design and Development of Aquaponics Piping System for Urban Farming - VIGIYEN, SARVIN; A M Leman, (Progress in Engineering Application and Technology, 2023)
Aquaponics is a system which for food production using aquaculture and hydroponics as cultivate fish and plant without soil. The fish and plant have created a low-cost symbiotic cycle. Fish waste (ammonia) is given to the plant bed in an aquaponic system, which functions as a biofilter and removes nitrate, an important nutrient for plant growth. Returning the fresh water to the fish tank, the cycle begins again aquaponic systems use less water than standard irrigation systems, which is a distinct benefit. The constant recirculation of water between the plant bed and the fish habitat helps save water. Aquaponics also has the advantage of providing organic fertilizer for plants through dissolved fish waste. Water quality monitoring is reduced when plants are used as a natural alternative to conventional filters. In this project, we develop a Nutrient Film Technique aquaponic system in three design by using the SOLIDWORK software as purpose to choose a best selection of designing that can make maximum nutrient production and affordable cost. To overcome the problem, the study brings into focus that need to be given top consideration in the process of selecting an effective design plan. The aquatic creatures are tilapia and catfish while the hydroponic plants are lettuce, spinach and basil which was highly recommended for this project. The project would have a huge influence on the surrounding area. Aquaponics' produce is undeniably healthy, and health-conscious people will undoubtedly reap the benefits of this endeavor.